ANALISIS KESIAPAN DAN STRATEGI IMPLEMENTASI TANDA TANGAN ELEKTRONIK PASIEN PADA REKAM MEDIS ELEKTRONIK DI RSUD BHAKTI DHARMA HUSADA SURABAYA - sulissetyaningrum, ivana; rabbani, auliyaur (LPPM Universitas Awal Bros, 2026)
The implementation of Electronic Medical Records (EMR) is an important part of digital transformation in healthcare services. However, several patient approval documents are still signed manually, causing inefficiency in paperless services. This study aimed to analyze the readiness and implementation strategies of patient electronic signatures on Electronic Medical Records at RSUD Bhakti Dharma Husada Surabaya. This research used a descriptive quantitative method with the Normalization Process Theory (NPT) approach including coherence, cognitive participation, collective action, and reflexive monitoring variables. Data collection was conducted using questionnaires distributed to 84 respondents consisting of health workers and related staff. The results showed that all variables were categorized as ready, with average scores of coherence 4.0437, cognitive participation 4.0357, collective action 4.0125, and reflexive monitoring 4.1190. The main obstacle was identified in the skill set workability aspect related to technical staff skills in assisting patients with digital devices. The priority implementation strategy was strengthening data security and system legality with an average score of 4.2976. Other strategies included patient education, preparation of standard operating procedures, infrastructure provision, human resource training, and SIMRS integration. RSUD Bhakti Dharma Husada Surabaya was considered ready to implement patient electronic signatures gradually by considering aspects of security, legality, infrastructure, and human resource readiness.